Microbispora soli sp. nov., isolated from soil of a hot spring - Suchada Kittisrisopit; Pattama Pittayakhajonwut; Sarin Tadtong; Chitti Thawai (My University, 2018)
A novel actinomycete, strain RTBAU4-9T, which produced longitudinally paired spores on aerial mycelia, was isolated from a soil sample of a hot spring area. This strain exhibited chemotaxonomic and genotypic properties typical of the genus Microbispora, such as meso-diaminopimelic acid in the cell-wall peptidoglycan, glucose, ribose and trace amount of madurose as the characteristic whole-cell sugars, phosphatidylethanolamine, diphosphatidylglycerol and phosphoglycolipids as the membrane phospholipids, MK-9(H4), MK-9(H2) and MK-9(H0) as the characteristic menaquinones, and iso-C16 : 0 and anteiso-C17 : 0 as the main fatty acids. The G+C content of the genomic DNA was 70.2 mol%. The result of 16S rRNA gene sequence analysis revealed the strain was a member of the genus Microbispora and was most closely related to Microbispora hainanensis 211020T (98.3 % 16S rRNA gene sequence similarity). In addition, the low percentage of DNA-DNA relatedness (<28.1±1.2 %) and several phenotypic differences confirmed that strain RTBAU4-9T should be considered as representing a novel species of the genus Microbispora, for which the name Microbispora soli sp. nov. is proposed. The type strain is RTBAU4-9T (=TBRC 7648T=NBRC 113147T).
Keywords: Diaminopimelic acid; Strain (injury); Chemotaxonomy; Genomics and Phylogenetic Studies